Galectin-3 is associated with arterial stiffness among hemodialysis patients. (27th February 2019) - Zhang, Qi; Yin, Kanhua; Zhu, Mingli; Lin, Xinghui; Fang, Yan; Lu, Jiayue; Li, Zhenyuan; Ni, Zhaohui
Aim: To evaluate the association between galectin-3 and arterial stiffness among hemodialysis patients.Methods: We enrolled 311 patients (median age: 61 years) with a median hemodialysis time of 90 months and a mean galectin-3 concentration of 29.78 ng/ml. Ninety-six (30.7%) had arterial stiffness diagnosed by the pulse-wave velocity over 10 m/s.Results: Galectin-3 was significantly associated with dialysis vintage, calcium, phosphorus and low-density lipoprotein. After adjustment for multiple cardiovascular risk factors, galectin-3 was independently associated with the pulse-wave velocity (partial r = 0.130; p = 0.035). This effect was still significant after additional adjustment for mean arterial pressure and single-pool Kt/V (partial r = 0.139; p = 0.014).Conclusion: Galectin-3 is independently associated with arterial stiffness among hemodialysis patients.